Disease activity assessment in systemic lupus erythematosus - Lin, Angela; Wakhlu, Ambika; Connelly, Kathryn (Frontiers in Lupus, 2024)
Systemic lupus erythematosus (SLE, lupus) is a chronic autoimmune disease characterised by a heterogeneous clinical presentation and complex underlying immunologic dysfunction. This poses a significant challenge to the accurate assessment of disease activity, which is central to both clinical management and research in SLE. This review aims to describe common barriers to accurately measuring disease activity in SLE and different approaches to disease activity assessment. We will cover the evaluation of disease activity in clinical practice and discuss the role of widely used and emerging disease activity instruments in both clinical and research contexts, including measures of flare, treat-to-target disease states and clinical trial endpoints.